Transition and Regional Inequality in Russia : Reorganization or Procrastination? - Dolinskaya, Irina (IMF Working Papers; Working Paper, 2002)
This paper analyzes the evolution of interregional income inequality during transition in Russia. The transition matrix approach reveals that between 1991 and 1997 income mobility tended toward a highly uneven long-term distribution with the majority of regions at low income levels and a minority of higher-income regions, in sharp contrast to pretransition times. The ordered logit analysis suggests that the more successful regions prospered on account of their natural resources, while continuing to resist economic reorganization by supporting traditional enterprises. The less-successful regions appeared trapped at low income levels due to uncompetitive industries and lack of resources needed for restructuring.